PEMANFAATAN INTERNET BERBASIS SWADAYA MASYARAKAT UNTUK AKTIVITAS PEMBELAJARAN DARING SISWA SEKOLAH - Rahman Sopian; Nandang Rukanda (IKIP Siliwangi, 2021)
This research is motivated by the occurrence of the COVID-19 pandemic so that the government has implemented large-scale social distancing, one of the areas affected by this application in the field of education. so that learning that was previously carried out in the classroom has now become online learning so that new problems arise in the field. This study aims to determine the use of self-help-based internet on the effectiveness of online learning for school students. The theoretical basis in this research 1. Theory of Online Learning 2. Theory of Self-help 3. Theory of Community Education. The data collection technique used a qualitative approach with the type of case study research and tend of descriptive. The instruments of this research are interviews, observations, and literature studies. This research was conducted at RT 02 RW 08 Sukatani Village, Ngamprah District, West Bandung Regency. Samples were taken of 5 people, namely 1 manager, 2 parents, and 2 students The results showed that the existence of non-government-based internet can increase the efficiency and effectiveness of students in online learning as well as save costs.